Structural characterization of 1, 3-bis-tert-butyl monocyclic benzene derivatives with agonistic activity towards retinoid X receptor alpha. (15th January 2023) - Kodama, Susumu; Matsumoto, Shuzo; Takamura, Yuta; Fujihara, Michiko; Watanabe, Masaki; Ono, Atsushi; Kakuta, Hiroki
Abstract: Retinoid X receptor alpha (RXRα) plays pivotal roles in multiple biological processes, but limited information is available on the structural features of chemicals that show low affinity for RXRα, but nevertheless cause significant activation, though these may represent a human health hazard. We recently discovered that several industrial chemicals having 1, 3-bis- tert -butylbenzene as a common chemical structure exhibit agonistic activity towards rat RXRα. In this study, we explored the structure-activity relationship of 1, 3-bis- tert -butyl monocyclic benzene derivatives for RXRα activation by means of  in vitro and in silico analyses. The results indicate that a bulky substituent at the 5-position is favorable for agonistic activity towards human RXRα. Since 1, 3-bis -tert -butyl monocyclic benzene derivatives with bulky hydrophobic moieties differ structurally from known RXRα ligands such as 9- cis -retinoic acid and bexarotene, our findings may be helpful for the development of structural alerts in the safety evaluation of industrial chemicals for RXRα-based toxicity to living organisms. Graphical Abstract: ga1 Highlights: 1, 3-Bis- tert -butyl monocyclic benzene structure features in a variety of industrial chemicals. Compounds containing 1, 3-bis- tert -butyl monocyclic benzene structure exhibit RXRα-agonistic activity. A bulky substituent at the 5-position of 1, 3-bis- tert -butylbenzene is favorable for agonistic activity towards RXRα.